Gut Colonization by Methanogenic Archaea Is Associated with Organic Dairy Consumption in Children - van de Pol, Jeroen A. A.; van Best, Niels; Mbakwa, Catherine A.; Thijs, Carel; Savelkoul, Paul H.; Arts, Ilja C. W.; Hornef, Mathias W.; Mommers, Monique; Penders, John (Frontiers in Microbiology, 2017)
The gut microbiota represents a complex and diverse ecosystem with a profound impact on human health, promoting immune maturation, and host metabolism as well as colonization resistance. Important members that have often been disregarded are the methanogenic archaea. Methanogenic archaea reduce hydrogen levels via the production of methane, thereby stimulating food fermentation by saccharolytic bacteria. On the other hand, colonization by archaea has been suggested to promote a number of gastrointestinal and metabolic diseases such as colorectal cancer, inflammatory bowel disease, and obesity. Archaea have been shown to be absent during infancy while omnipresent in school-aged children, suggesting that colonization may result from environmental exposure during childhood. The factors that determine the acquisition of methanogenic archaea, however, have remained undefined. Therefore, we aimed to explore determinants associated with the acquisition of the two main gastrointestinal archaeal species, Methanobrevibacter smithii and Methanosphaera stadtmanae, in children. Within the context of the KOALA Birth Cohort Study, fecal samples from 472 children aged 6-10 years were analyzed for the abundance of M.smithii and M.stadtmanae using qPCR. Environmental factors such as diet, lifestyle, hygiene, child rearing and medication were recorded by repeated questionnaires. The relationship between these determinants and the presence and abundance of archaea was analyzed by logistic and linear regression respectively. 369 out of the 472 children (78.2%) were colonized by M. smithii, and 39 out of the 472 children (8.3%) by M.stadtmanae. The consumption of organic yogurt (odds ratio: 4.25, CI95: 1.51; 11.95) and the consumption of organic milk (odds ratio: 5.58, CI95: 1.83; 17.01) were positively associated with the presence of M.smithii. We subsequently screened raw milk, processed milk and yogurt samples for methanogens. We identified milk products as possible source for M.smithii, but not M.stadtmanae. In conclusion, M.smithii seems present in milk products and their consumption may determine archaeal gut colonization in children. For the first time, a large variety of determinants have been explored in association with gut colonization by methanogenic archaea. Although more information is needed to confirm and unravel the mechanisms in detail, it provides new insights on microbial colonization processes in early life.